Phloridzin improves lipoprotein lipase activity in stress-loaded mice via AMPK phosphorylation. (November 2014) - Wang, Guo-En; Li, Yi-Fang; Wu, Yan-Ping; Tsoi, Bun; Zhang, Shi-Jie; Cao, Ling-Fang; Kurihara, Hiroshi; He, Rong-Rong
Abstract Long-term stress exposure can lead to disturbed homeostasis and cause many life-style diseases. Phloridzin possesses various bioactivities, but the understanding of the effects of phloridzin on stress-related lipid metabolism disorder is limited. Our results demonstrate that phloridzin improved plasma lipoprotein lipase (LPL) activity and triglyceride metabolism in restrained mice. A decrease of angiopoietin-like protein 4 (ANGPTL4) mRNA expression and an increase of AMP-activated protein kinase (AMPK) phosphorylation were observed after phloridzin treatment. After inhibiting AMPK phosphorylation, the effects of phloridzin on the amelioration of plasma LPL activity and suppression of ANGPTL4 expression were blocked. In addition, cardiac AMPK phosphorylation, plasma LPL activity and ANGPTL4 expression were also affected by phloridzin, even if the glucocorticoid receptor was blocked. Taken together, the down-regulation of ANGPTL4 expression by phloridzin was probably via a direct activation of AMPK pathway. This discovery can provide a biochemical and nutritional basis for the use of phloridzin-containing food and beverage in daily life.